Efeitos de populações e métodos de plantio na qualidade e rendimento da cultura de alho-porro - de Brito Giordano, Leonardo; P Campos , Joênes; de P Castro Filho, Fransisco; Senna Neto, Nicolau (Revista Ceres, 2025)
This experiment was conductedto test the later planting method less commonly used by the Brazilian farmers. Various plant spacings were also tested. The experiment was carried outatthe Horticulture Experimental Farm of ESA, UFV (Vigosa, Minas Gerais, Brazil); and lasted a period of seven months. The methods of planting tested have not affected the production. When the transplant were laid down, longer pseudostalks were produced.